2017
DOI: 10.1016/j.ufug.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Access to parks and physical activity: An eight country comparison

Abstract: Several systematic reviews have reported mixed associations between access to parks and physical activity, and suggest that this is due to inconsistencies in the study methods or differences across countries. An international study using consistent methods is needed to investigate the association between access to parks and physical activity. The International Physical Activity and Environment Network (IPEN) Adult Study is a multi-country cross-sectional study using a common design and consistent methods. Acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 46 publications
8
115
3
1
Order By: Relevance
“…In contrast, land use mix and connectivity had inverse impacts on sense of community, implying that these two characters had more complicated associations between physical and mental health. Further, the number of parks within the community was related to VPA as expected, because parks in the neighborhood can facilitate engagement in leisure-time physical activity [47]. In addition to the park, this study added other service facilities that might encourage recreational physical activity [48], including gyms, outdoor sports venues, and fitness places, which also showed positive associations.…”
Section: Direct Effect Of Environmentmentioning
confidence: 58%
“…In contrast, land use mix and connectivity had inverse impacts on sense of community, implying that these two characters had more complicated associations between physical and mental health. Further, the number of parks within the community was related to VPA as expected, because parks in the neighborhood can facilitate engagement in leisure-time physical activity [47]. In addition to the park, this study added other service facilities that might encourage recreational physical activity [48], including gyms, outdoor sports venues, and fitness places, which also showed positive associations.…”
Section: Direct Effect Of Environmentmentioning
confidence: 58%
“…This is why cities should show a greater proportion of green spaces and leisure areas in relation to the meters built [52]. We must increase the number of parks per inhabitant in such a way that all citizens have a nearby recreational area (less than 1 km), with easy access on foot or by bicycle [53][54][55]. In this sense, pocket parks seem to be an effective and economical solution [56].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported associations between access to parks and PA [53]. In total, 6181 people from 12 cities in 8 different countries participated in The International Physical Activity and Environment Network (IPEN) Adult Study, which determined that living near a park (less than 1 km) can contribute with up to 1/6 of the PA recommended per week.…”
Section: Opportunities Of Physical Activity With Cognitive Load Offermentioning
confidence: 99%
“…Novel strategies have been implemented to facilitate interaction with green spaces including community walking maps [25] and social walking groups [26], to discourage sedentary behaviour and help older adults reap the health benefits from these surroundings and social interactions. Having a greater abundance of parks, located within close proximity to older people's homes may be one solution to increase physical activity [27]. However, overcoming challenges in maintaining parks that are safe, accessible, clean, attractive and nuisance-free, may determine the extent to which public green spaces are utilised [6].…”
Section: Introductionmentioning
confidence: 99%